KEPEMIMPINAN DALAM PERSPEKTIF GENDER SERTA PERANNYA DALAM PENGEMBANGAN BISNIS - Dwi Susanti, Rizki Aprilia; Kusumaning Budi, Citra Setyaniwahyu (Unitri Press, 2023)
Historically, male leadership has been more dominant than female leadership. But today, women cannot always be seen as side workers, they are able to make their own choices, especially in business. The role of women sensitive to micro-enterprises in the Indonesian economy is gradually becoming the